One Hundred Twenty Years of Koala Retrovirus Evolution Determined from Museum Skins - Avila-Arcos, M.; Ho, S.; Ishida, Y.; Nikolaidis, N.; Tsangaras, K.; Honig, K.; Medina, R.; Rasmussen, M.; Fordyce, S.; Calvignac-Spencer, S.; Willerslev, E.; Gilbert, Thomas; et al. (Oxford Univ Press, 2013)
Although endogenous retroviruses are common across vertebrate genomes, the koala retrovirus (KoRV) is the only retrovirus known to be currently invading the germ line of its host. KoRV is believed to have first infected koalas in northern Australia less than two centuries ago. We examined KoRV in 28 koala museum skins collected in the late 19th and 20th centuries and deep sequenced the complete proviral envelope region from five northern Australian specimens. Strikingly, KoRV env sequences were conserved among koalas collected over the span of a century, and two functional motifs that affect viral infectivity were fixed across the museum koala specimens. We detected only 20 env polymorphisms among the koalas, likely representing derived mutations subject to purifying selection. Among northern Australian koalas, KoRV was already ubiquitous by the late 19th century, suggesting that KoRV evolved and spread among koala populations more slowly than previously believed. Given that museum and modern koalas share nearly identical KoRV sequences, it is likely that koala populations, for more than a century, have experienced increased susceptibility to diseases caused by viral pathogenesis.